Influence of environmental stress on microalgae growth and lipid profile: a systematic review - Suparmaniam, U. (Springer Science and Business Media B.V., 2022)
Microalgae biomass has attracted great interest from researchers as a promising feedstock for biodiesel production. Although enormous research works have been carried out to identify microalgae species with high biomass and lipid productivities, genetic modification of strains as well as optimization of cultivation conditions, however, the progress is yet to be fully satisfied. Based on the present lipid yield and extraction methods, it is still not feasible to commercialize the microalgae biodiesel. One of the promising approaches to elevate lipid accumulation by microalgae is through tuning the cellular mechanisms and metabolic pathway by exposing microalgae cells to various abiotic stress environments such as nutrient starvation, high salinity level and strong light intensity. Nevertheless, a comprehensive analysis of quantitative influences of critical abiotic stress on both microalgae biomass and lipid profile is still limited in the literature. Hence, the present paper aims to deliver insights into selections of single and multiple abiotic stress factors for simultaneous enhancement of microalgae biomass and lipids (polar and non-polar) which could improve the techno-economic viability in the microalgae processing chains and biorefinery industries. Graphical abstract: Figure not available: see fulltext. Â© 2022, The Author(s), under exclusive licence to Springer Nature B.V.